Secrecy and democracy - "Turner, Admiral Stansfield" (London, 1986)
The director of the CIA during the Carter administration explores past abuses of the U.S. intelligence apparatus, describes the radically redesigned system structured to avoid such abuses, and analyzes the problems besetting the intelligence community when he became CIA director in 1977.
Keywords: CIA